Intractable Erectile Dysfunction In A Depressed Elderly Man With Metabolic Syndrome On Multiple Medications: A Case Report - Nurul Hazwani, Hatta; Ai Ling, Ang; Hatta, Sidi (UPM Press, 2025)
Erectile dysfunction (ED) is a common sexual dysfunction (SD) and is known as an indicator of early mortality. The recurrence and persistence of ED is a major therapeutic challenge among physicians worldwide. The mechanisms of ED are multifactorial with biopsychosocial factors playing a role in the mediation of the SD. We presented a case of a 55-year-old man with history of metabolic syndrome who suffered from persistent ED despite treatment with oral phosphodiesterase-5 inhibitors (PDE5i). He was also suffering from clinical depression besides having diabetes mellitus, hypertension, abdominal obesity, hyperuricemia, and dyslipidaemia. His ED persisted despite being on a medication and being normotensive with normal total cholesterol level and well-controlled blood sugar. There is most likely an association of the risk of ED with multiple medications, especially with the statin and the antidepressants, based on the patient’s own validation. The therapeutic challenges are discussed in this report.